2003
DOI: 10.1183/09031936.03.00077902
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammation in COPD: physiological outcome measures and induced sputum

Abstract: Chronic obstructive pulmonary disease (COPD) is a result of airway inflammation, and the best predictor of COPD is the early detection of airflow limitation by spirometry. The Global Initiative for Obstructive Lung Disease Workshop Report defines airflow limitation using simple spirometric indices. Available guidelines categorise the severity of COPD using forced expiratory volume in one second (FEV1) and forced vital capacity (FVC), with symptoms playing a minor role in the assessment.Current standards define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 130 publications
0
20
0
1
Order By: Relevance
“…Accordingly, these measurements may be unreliable and variable if suboptimal maneuvers are performed (26). Moreover, some patients are not able to reliably perform spirometry because it requires good subject cooperation and maximal effort (7). It was also observed that spirometric exams can lead to temporary alteration in bronchomotor tone due to the deep inspiration required, which can have implications for respiratory mechanics measurements (26).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, these measurements may be unreliable and variable if suboptimal maneuvers are performed (26). Moreover, some patients are not able to reliably perform spirometry because it requires good subject cooperation and maximal effort (7). It was also observed that spirometric exams can lead to temporary alteration in bronchomotor tone due to the deep inspiration required, which can have implications for respiratory mechanics measurements (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, the modifications to respiratory mechanics are not always detected by this test (Coe et al 1989). Moreover, some patients are not able to reliably perform spirometry, as the methods require good subject co-operation and maximal effort (Crapo et al, 2003). Whole-body plethysmography features a more complex method in which the individual must remain isolated from the external environment, breathing spontaneously within a hermetically sealed box (ATS/ERS, 2005).…”
Section: Short Review Of Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…Recommendations for research in COPD (Croxton et al, 2002) include the need for improved noninvasive mechanical tests of lung function. In this context, FOT was suggested by Crapo et al (2003) as an attractive alternative for diagnosing obstruction in COPD, as it requires little patient effort and cooperation. A brief description of this technique is provided in the next section.…”
Section: Short Review Of Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…Sputum induction is a practical and safe procedure and an important research tool of local inflammation in the lung [4]. Recently, a significant body of data has accumulated regarding differences in sputum characteristics between COPD patients and healthy smokers, which could serve as markers for COPD susceptibility [9][10]. Inflammatory cell populations and subpopulations in sputum cellular phase can be easily studied using chemical and immunocytochemical methods.…”
Section: Induced Sputummentioning
confidence: 99%